Lifecycle assessment of a stapling machine - Dunmade, Israel (International Journal of Engineering and Technology, 2014)
A stapler is a mechanical device used to join two or more sheets of paper together by driving a thin metal staple through the sheets. They are widely used in schools, offices, business, government and homes. The anticipated large quantity of waste that is disposed of annually present great risk of environmental pollution and opportunities for economically viable resource recycling. This study evaluates potential environmental impacts of a Stapling machine and its end-of-life management opportunities. Environmental lifecycle assessment (LCA) process was used for the evaluation. The assessment was implemented with the aid of SimaPro software version 7.3.3.Results of the analyses revealed that climate change and eutrophication are the significant potential environmental impacts. Each Stapler has 1.265130 kg CO2-eq in Global Warming Potential and 0.113067 max kg O2-eq as its Eutrophication Potential. Further examination also showed that most of the impacts are from material selection, product distribution, and end-of-life management of the stapling machine. This study provides insights on potential environmental impacts of stapling machines and potential opportunities for improvements in their end-of-life management.